Down‐regulation of MYH10 driven by chromosome 17p13.1 deletion promotes hepatocellular carcinoma metastasis through activation of the EGFR pathway. Issue 24 (4th November 2021) - Jin, Qian; Cheng, Min; Xia, Xia; Han, Yuqing; Zhang, Jing; Cao, Pengbo; Zhou, Gangqiao
Abstract: Somatic copy number alterations (CNAs) are a genomic hallmark of cancers. Among them, the chromosome 17p13.1 deletions are recurrent in hepatocellular carcinoma (HCC). Here, utilizing an integrative omics analysis, we screened out a novel tumour suppressor gene within 17p13.1, myosin heavy chain 10 ( MYH10 ). We observed frequent deletions (~38%) and significant down‐regulation of MYH10 in primary HCC tissues. Deletion or decreased expression of MYH10 was a potential indicator of poor outcomes in HCC patients. Knockdown of MYH10  significantly promotes HCC cell migration and invasion in vitro, and overexpression of MYH10 exhibits opposite effects. Further, inhibition of MYH10  markedly potentiates HCC metastasis in vivo. We preliminarily elucidated the mechanism by which loss of MYH10 promotes HCC metastasis by facilitating EGFR pathway activation. In conclusion, our study suggests that MYH10, a candidate target gene for 17p13 deletion, acts as a tumour suppressor and may serve as a potential prognostic indicator for HCC patients.